Types of Human Papillomavirus (HPV) in Patients with ASCUS Pap Smear - H Hassani; M Javadian; M Raanaei; A Abedi; Sh Yazdani (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2022)
Background and Objective: Human papillomavirus (HPV) is one of the common infectious and pathogenic agents, and some of its genotypes have the ability to cause malignant changes in the surface of mucous cells. By examining the prevalence of HPV in atypical squamous cells of undetermined significance (ASCUS) Pap smear according to the risk factors, we can make a more correct decision in choosing the evaluation method and directing the patient to report the ASCUS lesion. Therefore, the aim of this study is to investigate the types of human papillomavirus (HPV) in patients with ASCUS Pap smear. Methods: This cross-sectional study was conducted on 200 patients with ASCUS pap smear results and HPV test referred to the colposcopy clinic of Babol Ayatollah Rouhani Hospital during the last two years. Demographic information, history of obstetrics, history of OCP use, history of STD disease and high-risk behaviors, cervical treatments, HPV typing, Pap smear, colposcopy and cervical biopsy results were recorded and analyzed. Findings: The mean age of the patients was 33.83±8.09 years, and ASCUS pap smear showed 129 cases (64.5%) of high-risk papillomavirus, 16 cases (0.8%) of low-risk papillomavirus and 55 cases (27.5%) of both types. Cervical intraepithelial neoplasia grade 2 was in 18 cases (0.9%), cervical intraepithelial neoplasia grade 1 in 10 cases (0.5%) and cervical intraepithelial neoplasia grade 3 in 2 cases (0.1%). 17.1% of high-risk viruses caused cervical neoplasm. None of the low-risk viruses led to neoplasms and all of them were inflammatory. In both high-risk and low-risk cases, 14.5% neoplasm was seen. However, the relationship between the type of papillomavirus and the incidence of neoplasm was significant (p=0.058). Conclusion: Based on the results of this study, the ASCUS pap smear needs more detailed investigation such as colposcopy and cervical biopsy under the supervision of experts because it is associated with the high-risk HPV virus in many cases.